Membuat Aplikasi Penjualan Pada CV. Sumber Bakti Mandiri Berbasis Website Menggunakan PHP dan MYSQL - M Rusdi; Kadarsih; Wisnumurti (Universitas Mahakarya Asia, 2022)
The development of technology today, especially information technology is growing very rapidly. Nowadays we often hear about internet technology which is the latest development of information technology. The development of internet technology is currently more developed towards user friendly, which means that it makes it easier for users to understand and carry out internet functions. In the business world, especially in the field of marketing, the internet is one of the global marketing media. In the information age that is global in nature, information can be easily and quickly disseminated and obtained. CV.Sumber Bakti Mandiri is a subsidiary of Anita Group that sells various kinds of smartphones, laptops, printers, and various other accessories. in buying and selling CV.Sumber Bakti Mandiri still input data manually using handwritten receipts, making it too difficult to process sales data. In this case, the problem that becomes the object of research, namely CV Sumber Bakti Mandiri, is how to design web-based information so that an order process can be fulfilled according to a predetermined time and can create extensive communication between sellers and buyers. Therefore, to support these efforts, a web-based product sales application was designed for the company.